Worldviews education: cosmopolitan peacebuilding and preventing violent extremism. Issue 3 (3rd July 2019) - Halafoff, Anna; Lam, Kim; Bouma, Gary
ABSTRACT: Since the mid-2000s soft power approaches to counter and prevent violent extremism (C/PVE) have increasingly been implemented by civil society, state actors and UN agencies internationally. Education is a critical and previously undervalued component in PVE, as it has only recently begun to attract significant scholarly and policy attention. This article briefly reviews the emerging field of education and PVE, and argues that it could benefit from drawing on insights from research on education about diverse religious and non-religious worldviews and PVE in Australia. Our research indicates that these types of educational initiatives can assist with addressing religious vilification, discrimination and interreligious tensions, and also with building religious literacy and social inclusion of young people, thereby minimising risks of alienation and vulnerability to extremism. We also argue that a critical approach to education about religions can assist young people to identify religions' ambivalent role in contributing to both cultures of violence – direct and structural – and cultures of peace. We present a case study on learning about diverse worldviews in Victoria, Australia in this article to illustrate our arguments and finally make a series of recommendations regarding religion, education and PVE, and cosmopolitan peacebuilding strategies more broadly.